(untitled) ("Temas Sociais" Journal, 2026)
Migrations represent a significant part of human history, influencing social, economic, demographic, and cultural changes while also playing a fundamental role in the growth of global society. Currently, we are experiencing a radical transformation in migration flow patterns. Portuguese society is no exception: it is diverse and becoming increasingly plural, reflected, among other aspects, in the significant presence of migrants from different cultural, ethnic, and social backgrounds. This diversity should be understood broadly, encompassing cultural dimensions as well as bio-social dimensions. In the context of Social Work intervention with migrant populations, this diversity manifests in the needs and challenges faced by these individuals, requiring both technical and relational skills, as well as a deep understanding of the social, economic, and cultural dynamics shaping migration flows. To better understand these dynamics, a semi-structured interview was conducted with Professor Jorge Malheiros, a specialist in Migration Studies, aiming to identify the main challenges and impacts of superdiversity in Portuguese society. The interview was carried out by final-year Social Work students under the guidance of Professor Hélia Bracons.